3D Printing of a Medical Device Designed for Sustained Drug Delivery to the Ear - Rizg, Waleed (2020)
Ear infections are a common ear problem that can affect the human ear at all ages. Otitis externa (OE) is an external inflammatory ear condition of the outer auditory canal with or without an ear infection. Such ear inflammation might be located within the auditory canal with or without the involvement of the ear pinna or tragus. Most acute otitis externa (AOE) can be treated with over-the-counter ear drops, and in severe cases, patients may need to take oral or intravenous antibiotics. Topical ear drops are preferred for many reasons, including the ability to directly deliver them to the site of action with a higher local drug concentration, reduced ototoxicity, the ability to bypass the blood labyrinth barrier (BLB), less possibility of bacterial antibiotic resistance, and reduced systemic side effects. However, otic drops have limitations, including the frequency of daily dosing, whereby the patient has to lie down, and a reduction in the ease of self-administration. Ototopical treatments with a gelling system via the external ear canal can provide advantages over-ear drops, including improved patient compliance by reducing the frequency of daily dosing, increased contact time of the administered drug at the site of action, prolonged release of the drug at the desired site of action, and no need for the patient to lie down to prevent the drug escaping from the outer ear. We propose to develop an in-ear prototype device using 3D printing to deliver dexamethasone (DXM) as an anti-inflammatory medication through a hydroxypropyl methylcellulose (HPMC) gelling system to the external ear canal. DXM would be able to show a sustained release after being inserted into a patient’s external canal for the treatment of AOE. In chapter three, various ear prototype devices with a range of basic and realistic geometries were successfully printed using two kinds of 3D printing technologies, including fused deposition modelling (FDM) and stereolithography (SLA). FDM was successfully utilised with a PLA thread to develop an in-ear prototype device with pores to facilitate drug release. Electron microscopy confirmed that the FDM-printed PLA devices have uniformly distributed layers without cracking or unwanted pores between the deposited layers. Also, there were no overlaps between the printed layers. After the proper design was reached, various concentrations of HPMC hydrogels were successfully prepared. The rheological data show that the concentrations of the prepared HPMC samples (1-6% HPMC w/w) have liquid-like behaviours. In comparison, the 7% HPMC w/w sample showed an elastic-like behaviour after 15 Hz frequency. Furthermore, the flow curve data showed that the HPMC samples exhibited non-Newtonian shear-thinning behaviours. The releases of the HPMC hydrogel samples (1-7% HPMC w/w) through various FDM PLA printed ear prototype devices with simple geometries containing various pore numbers and locations were affected by different factors, including increasing the pore numbers, decreasing the concentrations of the HPMC polymer, raising the temperature from room temperature to body temperature, and changing the pore locations of the prototype devices. The 7% HPMC was selected to be utilised with the developed ear prototype device as a vehicle for the extended drug release of DXM. In the final experimental chapter, two tablets, including DXM/methyl-β-cyclodextrin and DXM-lactose, were successfully formulated. The manufactured tablets have the same dose of DXM used in the treatment regimen of OE patients (≈ 2 mg of DXM). The DXM successfully diffused through the selected 7% HPMC hydrogel according to the Raman data. The Raman results confirmed that the intensity and area under the curve (AUC) of the characterised molecular peak of the C=O group, located at 1660 cm-1, decreased from day 1 to day 7. Finally, the in vitro release experiment showed that the DXM had a sustained release for the typical period of the treatment regimen for AOE, i.e. 7 days.